Motivasi dan keterampilan pemahaman terhadap kemampuan pemecahan masalah matematika dengan strategi think talk write - Putri Okti Rizqiyani; Wikan Budi Utami; Isnani (Universitas Muhammadiyah Purworejo, 2019)
This study aims to analyze how the influence of 1) motivation on mathematical problem solving skills with Think Talk Write strategy, 2) skills of understanding of mathematical problem solving skills with Think Talk Write strategies, 3) motivation and skills understanding of mathematical problem solving skills with Think Talk Write strategies. Data collection techniques carried out in the experimental class namely class VII D and class VII E using tests, questionnaires, and observations. The test instrument for problem solving ability amounted to 10 items, the questionnaire amounted to 30 items, while the observation instrument amounted to 15 items. Test instruments and questionnaires were first tested in the trial class that is class VII C to determine validity and reliability. Data analysis using a simple linear regression test and multiple regression, with a significance level of 5%. The results were obtained 1) motivation influences the ability of mathematical problem solving with Think Talk Write strategy with a degree of influence 60.59%, 2) comprehension skills affect the ability to solve mathematical problems with Think Talk Write strategies with an effect of 59.3%, 3) motivation and comprehension skills affect the ability to solve mathematical problems with the Think Talk Write strategy with a 65.99% effect.